Treatment of grade four hemorrhoids in a patient with acute myeloid leukemia with severe thrombocytopenia by laser hemorrhoidopexy: A case report (Indian Journal of Case Reports, 2024)
Here, we present the case of a 66-year-old female patient with acute myeloid leukemia and severe thrombocytopenia who came with the complaints of painful per anal mass and bleeding per rectum for 1 year. The patient is a known case of obesity, hypertension, and diabetes mellitus and has received three cycles of chemotherapy with decitabine. On examination, she was found to have fourth- degree hemorrhoids at 3, 7, and 11 oclock positions with acute edematous changes. We successfully treated this patient with laser hemorrhoidopexy, whereby laser energy was delivered to each hemorrhoidal cushion. While lasers for the successful treatment of grade 2 and 3 hemorrhoids are well documented in the literature, we successfully treated this patient with prolapsing fourth-degree hemorrhoids with just laser energy delivery. With these results, we would also like to consider laser hemorrhoidopexy as an effective treatment option for four-degree hemorrhoids for which open Milligan–Morgan hemorrhoidectomy and stapler hemorrhoidectomy are currently considered treatment options.